Fabrication of a nano polymer wrapping Meg3 ShRNA plasmid for the treatment of cerebral infarction. (5th November 2018) - Shen, Junyi; Zhao, Zhiming; Shang, Wei; Liu, Chunli; Zhang, Beibei; Xu, Zihan; Cai, Hui
Abstract: Cerebral infarction is with poorer prognosis and high rates of mortality. After cerebral infarction, the promoting angiogenesis can accelerate the recovery of neurological function. Long non-coding RNA (LncRNA) maternally expressed gene 3 (Meg3) was overexpressed in cerebral infarction area and the knockdown of Meg3 promotes neovascularization and improves nerve function. In this study, we fabricated a nano-polymer wrapped Meg3 short hairpin RNA (ShRNA) plasmid to knockdown Meg3 and conjugated with OX26 antibody (MPO) to realize the brain targeting for the treatment of cerebral infarction. The MPO particle size was 103 ± 11 nm (PDI = 0.27) detected by dynamic light scattering (DLS) and the zeta potential of MPO was −32 mV. MPO achieved brain microvascular endothelial cell (BMEC) targeting and enhanced endothelial cells migration ( p < .05), and tube formation ( p < .05) in vitro . MPO realized brain tissue target, reduced the volume of cerebral infarction ( p < .05) detected by TTC staining, increased capillary density through the HE staining and increased cerebral cortex micro-vessel through immunofluorescence method in vivo . The angiogenesis associated genes Vegfa, and Vegfr2 were upregulated after the treatment of MPO, compared with Meg3 or control plasmid treated group. This study suggested that MPO could achieve brain target and significantly promoted angiogenesis and became a new treatment method for cerebral infarction.